The agricultural sector as an alternative to illegal mining in Peru: A case study of Madre de Dios - Piñeiro, Valeria; Thomas, Jenny; Elverdin, Pablo (International Food Policy Research Institute, 2016)
Gold mining is the main economic activity in Madre de Dios, Peru. Despite efforts, the state has not yet managed to identify a formalization process achievable for small operators. In addition, many small-scale miners are driven by poverty and need income to provide for their basic needs. Because participation in small-scale mining is largely driven by poverty, it is likely that, in the longer term, much artisanal mining activity will disappear naturally if, through economic development, more attractive work options become available. This paper reviews the importance of illegal mining in Madre de Dios and the potential for development of the agriculture sector. It also analyzes three different policy scenarios: (1) government spending to rectify the environmental damage in the region caused by illegal mining, (2) development of the agricultural sector in the region, and (3) a final scenario with both environmental restoration and agricultural development. Results show that additional government spending in Madre de Dios does not significantly affect the rest of the country and that investment in agriculture can achieve structural change in the gross domestic product of Madre de Dios. Development of the agricultural sector also slightly increases household incomes in Madre de Dios.